Nicotine and endometrial decidual growth in pseudopregnant rats. (4th January 2014) - Siti Norashikin, M. T.; Ghosh, S.; Chatterjee, R.; Rajikin, M. H.; Chatterjee, A.
Abstract: Purpose: The present study aims to investigate the effects of nicotine on the endometrial decidual growth and levels of estrogen and progesterone in pseudopregnant rats. Methods: Pseudopregnancy (pc) was induced in cyclic Sprague‐Dawley rats by sterile mating. Subcutaneous injection of nicotine tartrate (7.5 mg/kg/day) was scheduled from day 1 through day 5, day 5 through day 9 or day 1 through day 9 of pc. In another group of pseudopregnant rats, concomitant treatment of nicotine tartrate concurrently with progesterone (2 mg/day) was scheduled from day 1 through day 9 pc. Control groups received subcutaneous injections of vehicle only. Endometrial decidualization was induced on day 5 pc. On day 10 pc, animals were sacrificed.The degree of decidual growth and circulating levels of estrogen and progesterone were measured. Results: The decidual growth in all the first three nicotine‐treated groups of animals was significantly reduced, particularly in the animals treated with nicotine from day 1 through day 9 pc. Plasma estrogen levels were significantly elevated in animals treated with nicotine from day 1 through day 9 pc. Conversely, levels of plasma progesterone were found to be significantly attenuated in the same group of nicotine‐treated animals compared to controls. Exogenous replacement of progesterone, however, caused a higher degree of endometrial decidualization compared to the nicotine‐treated group but it was slightly less than when compared to control. Conclusions: In conclusion, nicotine‐induced progesterone deficiency with a corresponding elevation of estrogen may possibly attenuate the degree of endometrial decidualization in pseudopregnant rats.